Breastfeeding Benefits and Resources: How do women become milk donors? - Angela Szymanski; Diana Hazard Taft (EDIS)
This publication is intended for a general audience from all educational backgrounds. It explains the process of becoming a donor to the Mothers’ Milk Bank of Florida and why the criteria for being a donor screens for things that are often safe when feeding your own infant. The authors would like to thank all those who consider becoming milk donors. We know it is a lot of work, and that Mothers’ Milk Bank of Florida can only accept donations from women who do not expect any compensation for the donated milk. Milk donors give the most fragile babies the gift of life: Thank you.